Efeito da aplicação do biocarvão nos atributos microbiologicos do solo, cultivado com teca, no bioma Amazônia - Mioranza, Mirelly (2016)
The biochar product is formed from the thermal decomposition of biomass in a closed environment by limited supply of oxygen and at relatively low temperatures and used as a soil conditioner. The aim of this study was to evaluate the use of biochar as a soil conditioner and its effect on the β- glucosidase activity, acid phosphatase and bacterial diversity in soil Teak experiment with fifteen and three months duration in a oxisol, located in Sinop - Mato Grosso, Brazil.The treatments were: T1 seedling without biocarvão ; T2 seedling with biocarvão; T3 seedling without biocarvão + activated biocarvão applied to the soil; T4 seedling with biocarvão + activated biocarvão applied to the soil; T5- seedling without biocarvão + biocarvão not activated applied to the soil; T6- seedling with biocarvão + biocarvão not activated applied to the soil. It determined the activity of two enzymes related to the cycle C and P and bacterial biodiversity was evaluated by DGGE technique using universal primers for the bacterial 16S rDNA region. There was no increase in the activity of β-glucosidase fifteen months after application of biochar, but its activated form accompanied by increased activity of this enzyme, unlike the acid phosphatase had a low activity in the first 3 months and after fifteen months on application of biochar in the soil the activity of this enzyme was higher. With regard to moisture and soil pH was not altered by the presence of biochar. The structure and diversity of the bacterial community in the soil suffered more pronounced influence of biochar fifteen months of soil application.